Relationship Between Complementary Feeding Practices And Stunting Incidence - Novianti, Eka; Sary, Lolita; Evrianasari, Nita; Rachmawati, Fijri (JKM (Jurnal Kebidanan Malahayati), 2025)
Latar Belakang  : Data Survei Status Gizi Indonesi (SSGI) oleh Kementrian Kesehatan RI tahun 2022 menunjukkan prevalensi stunting di Indonesia sebesar 21,6%, di Provinsi Lampung sebesar 15,2%, di Kabupaten Way Kanan sebesar 18,4%, di Kecamatan Negeri Agung sebesar 7,84% serta di wilayah kerja UPT Puskesmas Negeri Agung 8,25%. Survey pendahuluan yang peneliti lakukan pada bulan Februari 2023 belum semua ibu menerapkan praktik pemberian makanan pendamping ASI (MP-ASI) yang sesuai dengan rekomendasi WHO yaitu tepat waktu dalam pemberian MP-ASI, kualitas makanan MP-ASI yang adekuat, keamanan dalam menyiapkan dan menyimpan MP-ASI, dan responsif feeding.  Tujuan penelitian ini adalah  untuk mengetahui hubungan praktik pemberian makanan pendamping ASI dengan kejadian stunting.Metode : Metode yang digunakan  adalah observasi analitik dengan pendekatan cross sectional menggunakan data primer. Sampel dalam penelitian ini 211 responden dengan teknik pengambilan sampel accidental sampling, dimana pengumpulan data  menggunakan kuesioner kemudian dianalisa  dengan uji chi-square. Hasil : Dari hasil penelitian diperoleh terdapat hubungan yang signifikan ketepatan waktu dalam pemberian MP-ASI dengan kejadian stunting (p value 0,000), terdapat hubungan makanan pendamping ASI yang adekuat dengan kejadian stunting (p value 0,000),  terdapat hubungan yang signifikan keamanan pemberian MPASI yang adekuat dengan kejadian stunting (p value 0,000), terdapat hubungan yang signifikan responsive feeding dengan kejadian stunting (p value 0,000), balita dengan stunting menunjukkan dampak buruk terhadap pertumbuhan, perkembangan dan kualitas sumber daya manusia. Dari sektor kesehatan perlu adanya peningkatan upaya preventif dan promotif mengenai praktik pemberian MP-ASI sesuai dengan standar agar dapat memperbaiki status gizi anak dan mencegah dampak dari stunting. Stunting bukan hanya masalah sektor kesehatan, intervensi yang tepat dengan penanganan dini dan bertanggung jawab melalui berbagai lintas sektor terkait.Kesimpulan : Terdapat hubungan praktik pemberian makanan pendamping ASI dengan kejadian stunting. Kata kunci : Stunting, Praktik Pemberian MP-ASI,tepat waktu, adekuat, aman,responsive feeding ABSTRACT Background: The Indonesian Nutritional Status Survey (Survei Status Gizi Indonesia) conducted by the Ministry of Health of the Republic of Indonesia in 2022 indicated a prevalence of stunting in Indonesia at 21.6%. In Lampung Province, it was 15.2%; in Way Kanan Regency, 18.4%; in Negeri Agung District, 7.84%; and in the working area of UPT (Technical Implementation Unit) Negeri Agung Public Health Center, 8.25%. A preliminary survey conducted by the researcher in February 2023 revealed that not all mothers were implementing appropriate complementary feeding practices in accordance with WHO recommendations. These recommendations include timely initiation of complementary feeding, adequate quality of complementary foods, safe preparation and storage of complementary foods, and responsive feeding. The aim of this research was to determine the relationship between complementary feeding practices and the incidence of stunting.Method: The method used was analytical observation with a cross-sectional approach using primary data. The sample in this research comprised 211 respondents selected through an accidental sampling technique. Data was collected using a questionnaire and subsequently analyzed using the chi-square test. Results: From the research results, it was found that there was a significant relationship between the timely initiation of complementary feeding and stunting incidence (p-value 0.000). There was a significant association between appropriate complementary feeding practices and stunting incidence (p-value 0.000). Moreover, a significant relationship was observed between the safe provision of adequate complementary foods and stunting incidence (p-value 0.000) and a significant correlation between responsive feeding and stunting incidence (p-value 0.000). Stunted toddlers demonstrated adverse effects on growth, development, and human resource quality. In the healthcare sector, there is a need for an increase in preventive and promotive efforts regarding appropriate complementary feeding practices in accordance with standards. This is essential for improving children's nutritional status and preventing stunting's impacts. Stunting is not merely a healthcare sector issue; it demands appropriate interventions through early and responsible management across various interconnected sectors.Conclusion: There is a correlation between the practice of providing complementary foods alongside breastfeeding and the occurrence of stunting. Keywords: Stunting, Complementary Feeding Practices timely, adequate, safe, responsive feeding